Comparison of Thromboelastography and Conventional Coagulation Tests in Patients With Severe Liver Disease. (3rd June 2020) - Lloyd-Donald, Patryck; Vasudevan, Abhinav; Angus, Peter; Gow, Paul; Mårtensson, Johan; Glassford, Neil; Eastwood, Glenn M.; Hart, Graeme K.; Jones, Daryl; Weinberg, Laurence; Bellomo, Rinaldo
Objective: Thromboelastography (TEG) may provide rapid and clinically important coagulation information in acutely ill patients with chronic liver disease (CLD). Our objective was to describe the relationship between TEG and conventional coagulation tests (CCTs), which has not been previously explored in this population. Methods: In acutely ill patients with severe CLD (Child-Pugh score > 9, category C), we conducted a prospective observational study investigating coagulation assessment as measured by both CCTs and TEG. We used quantile regression to explore 30 associations between TEG parameters and corresponding CCTs. We compared TEG and CCT measures of coagulation initiation, clot formation, clot strength, and fibrinolysis. Results: We studied 34 patients on a total of 109 occasions. We observed inconsistent associations between TEG and CCT measures of coagulation initiation: TEG (citrated kaolin [CK] assay) standard reaction time and international normalized ratio: R 2 = 0.117 ( P = .044). Conversely, there were strong and consistent associations between tests of clot formation: TEG (CK) kinetics time and fibrinogen: R 2 = 0.202 ( P < .0001) and TEG (CK) α angle and fibrinogen 0.263 ( P < .0001). We also observed strong associations between tests of clot strength, specifically TEG MA and conventional fibrinogen levels, across all TEG assays: MA (CK) and fibrinogen: R 2 = 0.485 ( P < .0001). There were no associations between TEG and D-dimer levels. Conclusions: In acutely ill patients with CLD, there are strong and consistent associations between TEG measures of clot formation and clot strength and conventional fibrinogen levels. There are weak and/or inconsistent associations between TEG and all other conventional measures of coagulation.